Validation of a new model for the sizing of denitrification reactors, by testing full-scale plants. Issue 11 (3rd June 2017) - Raboni, M.; Torretta, V.
ABSTRACT: A new deterministic model for the calculation of the specific denitrification rate (SDNR), useful for the design of pre-denitrification reactors, was tested on eight full-scale activated sludge plants. The model represents the SDNR at 20°C (SDNR20°C ) as a function of the sludge loading in the denitrification reactor (F:MDEN ) and the residual dissolved oxygen in the denitrification reactor (DODEN ). The results proved the ability of the model in calculating the SDNR20°C . The model shows a lower degree of adaptability for small-sized plants. SDNR20°C proved to have a strong sensitivity to DODEN, mainly in correspondence with low DO concentrations (less than 2 mg L −1 ). The sensitivity decreases at greater DO values, but with a progressively less marked gradient, up to becoming weak only at DO concentrations greater than 0.4-0.5 mg L −1, which are rarely found in full-scale plants. DO concentrations measured in real-scale facilities are mostly in the range 0.2-0.4 mg L −1 . These concentrations cause adverse effects on the kinetics of nitrogen removal, and consequently on the denitrification performance. Thus, minimizing DO in the pre-denitrification reactor is relevant. The sensitivity of SDNR20°C to F:MDEN was less important, as it is characterized by a growing linear behaviour with a low slope.